Preparation and application method of porous adsorbent for removing hexavalent chromium in wastewater
By combining solid waste such as coal gangue and fly ash with foaming systems, the porous adsorbents are solved, and the cost of removing hexavalent chromium in printing and dyeing wastewater is difficult to regenerate, achieving high efficiency and low cost six-dimensional Valid chromium adsorption effect has good application prospects.
Patent Information
- Application Number
- CN202411524089.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art has high costs, difficult regeneration of adsorbents and complex operation in the process of removing hexavalent chromium from dyeing wastewater, resulting in increased processing difficulties and costs, and poses a threat to the environment and health.
By combining solid waste such as coal gangue, fly ash with foaming system and foam stabilizer, a porous adsorbent with rich pore structure and high specific surface area is prepared, which is used to efficiently adsorb hexavalent chromium in wastewater, which is easy to operate and Low cost.
It has achieved efficient removal of hexavalent chromium in wastewater, reduced treatment costs, and has good application prospects. Due to its structural characteristics, it can provide more adsorption active sites, significantly improving the adsorption effect of pollutants.
Smart Images

Figure BDA0005108728600000051 
Figure BDA0005108728600000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a preparation method and an application method of a porous adsorbent for removing hexavalent chromium from wastewater. Background Art
[0002] Hexavalent chromium is another important inorganic pollutant in printing and dyeing wastewater. Chromium exists in various valence states in nature, among which hexavalent chromium is the most toxic. Hexavalent chromium compounds are highly oxidizing and toxic, and can invade the human body through various pathways, such as the digestive tract, respiratory tract, skin and mucous membranes. Long-term contact or ingestion of hexavalent chromium may cause a variety of health problems, such as skin damage, respiratory diseases, digestive system diseases and even cancer. In the printing and dyeing process, hexavalent chromium may come from certain dyes or auxiliaries, or be converted from chromium in other valence states under certain conditions. Once entering the wastewater system, the presence of hexavalent chromium will greatly increase the difficulty and cost of wastewater treatment. At the same time, due to the high toxicity and stability of hexavalent chromium, its accumulation and migration in the environment may also lead to a wider range of ecological risks.
[0003] Hexavalent chromium in printing and dyeing wastewater poses a serious threat to the environment and human health. In order to reduce its emission and harm, a series of effective wastewater treatment measures and technologies, such as physical treatment, chemical treatment and biological treatment, need to be adopted to ensure that the wastewater can meet environmental protection standards before discharge.
[0004] Common methods for treating Cr(VI) are adsorption and photocatalytic oxidation, but the utilization rate of sunlight in photocatalytic oxidation is currently too low and the application conditions are limited. Due to its simple operation and environmental protection, adsorption has become a better way to treat Cr(VI).
[0005] However, the cost and regeneration of adsorbents are currently the main factors limiting the development of adsorption methods, and there is an urgent need to develop economical, efficient and regenerable adsorbents. Summary of the invention
[0006] The purpose of the present invention is to solve the above technical problems, and discloses a method for preparing a porous adsorbent for removing hexavalent chromium from wastewater and an application method thereof. The treatment method comprises the following steps: first, preparing a porous adsorbent capable of efficiently adsorbing hexavalent chromium, then adding the porous adsorbent to wastewater containing hexavalent chromium, and stirring for a certain period of time, so as to efficiently remove pollutants such as hexavalent chromium from the wastewater. The porous adsorbent prepared by the present invention is polymerized by solid wastes such as coal gangue and fly ash, and a foaming system and a foam stabilizing system are added during the polymerization process. The obtained porous adsorbent has a rich pore structure and a high pore area. The adsorbent surface has a large number of grooves, the interior has fine pores, and the specific surface area is large, which can provide more adsorption active sites. The present invention can simply and efficiently adsorb and remove hexavalent chromium in wastewater by preparing the porous adsorbent, has extremely low cost, is easy to operate, and has excellent application prospects.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] A porous adsorbent for removing hexavalent chromium from wastewater, comprising the following raw materials:
[0009] Powder: coal gangue, fly ash, slag; wherein the coal gangue, fly ash and slag account for 25-50 parts, and the total of the three is 100 parts.
[0010] Alkali activator: water glass, the mass ratio of water glass to powder is 3-5:10;
[0011] Foaming system: sodium nitrite, sodium dodecyl sulfate, ammonium chloride, foam stabilizer, catalyst, wherein the foaming system contains 100-150 parts of sodium nitrite, 10-30 parts of sodium dodecyl sulfate, 100-120 parts of ammonium chloride, 5-10 parts of foam stabilizer, and 25-40 parts of catalyst;
[0012] The foam stabilizer is xanthan gum or hydroxyethyl cellulose;
[0013] The catalyst is citric acid;
[0014] The mass ratio of the foaming system to the powder is 0.5-1:150.
[0015] Furthermore, the mass percentage of each component in the coal gangue is: SiO2: 60%-75%, Al2O3: 20%-28%, CaO: 0.1%-0.8%, K2O: 3%-3.8%, TiO2: 1%-1.5%;
[0016] The mass percentages of the components in the fly ash are: SiO2: 50%-55%, Al2O3: 20%-29%, CaO: 0.01%-0.5%, K2O: 1%-1.8%, TiO2: 2%-2.5%;
[0017] The mass percentage of each component in the slag is: SiO2: 30%-35%, Al2O3: 10%-16%, CaO: 30%-42%, K2O: 0.1%-0.5%, TiO2: 1%-1.7%.
[0018] Furthermore, the particle size of the coal gangue is less than 0.075 mm, and it needs to be calcined at 600-800° C. for 4-6 hours before use; the particle size of the fly ash is less than 0.075 mm, and the particle size of the slag is less than 0.075 mm.
[0019] Furthermore, the modulus of the water glass is 1.2-1.8, the solid content is 34wt%, and the Baume degree is 40.
[0020] A method for preparing a porous adsorbent for removing hexavalent chromium from wastewater comprises the following steps:
[0021] Step S1: Mix coal gangue, fly ash and slag in proportion to obtain powder A;
[0022] Step S2: stirring water glass and then standing to obtain an alkaline activator;
[0023] Step S3: mixing sodium nitrite, sodium dodecyl sulfate, ammonium chloride, a foam stabilizer and a catalyst in proportion to obtain a foaming system;
[0024] Step S4: adding the powder A obtained in step S1 to the alkali activator obtained in step S2; after mixing, mechanically stirring to obtain a mixed slurry B;
[0025] Step S5: adding the foaming system obtained in step S3 to the mixed slurry B obtained in step S4, and then mechanically stirring to obtain a mixed slurry C;
[0026] Step S6: then pouring the mixed slurry C into a silica gel mold, putting it into a sealed bag, and curing and solidifying it in a blast drying oven;
[0027] Step S7: The mold is taken out from the blast drying oven and cured at room temperature; after the curing is completed, the porous adsorbent is crushed into 30-50 meshes for standby use.
[0028] Furthermore, the alkaline activator is allowed to stand for 12-24 hours, the curing temperature of the blast drying oven is 50-80° C., and the curing time is 0.5-1.0 hour.
[0029] A method for applying a porous adsorbent in adsorbing hexavalent chromium comprises: mixing and stirring the porous adsorbent with wastewater; the wastewater is wastewater containing a hexavalent chromium solution.
[0030] Furthermore, the stirring time is 100-120 min.
[0031] Furthermore, the concentration of hexavalent chromium in the wastewater is 10-200 mg / L, the pH value is 1.5-10, and the peak value of the ultraviolet spectrum is 500-700 nm.
[0032] Furthermore, the dosage of the porous adsorbent is 50-500 mg / L, and the stirring rate is 800-1000 r / min.
[0033] The beneficial effects of the present invention are:
[0034] The invention discloses a preparation method and application method of a porous adsorbent for removing hexavalent chromium from wastewater. The treatment method comprises the following steps: first, preparing a porous adsorbent capable of efficiently adsorbing hexavalent chromium, then adding the porous adsorbent into wastewater containing hexavalent chromium, and stirring for a certain period of time, so as to efficiently remove pollutants such as hexavalent chromium from the wastewater. The porous adsorbent prepared by the invention is polymerized by solid wastes such as coal gangue and fly ash, and a foaming system and a foam stabilizing system are added during the polymerization process. The obtained porous adsorbent has a rich pore structure and a high pore area. The adsorbent surface has a large number of grooves, the interior has fine pores, the specific surface area is large, and more adsorption active sites can be provided. The invention can simply and efficiently adsorb and remove hexavalent chromium in wastewater by preparing the porous adsorbent, has extremely low cost, is easy to operate, and has excellent application prospects. DETAILED DESCRIPTION
[0035] The following will further describe the optimized implementation of the present invention. Although the following describes the optimized implementation of the present invention, it should be understood that the present invention can be implemented in various forms and should not be limited by the implementation described here. On the contrary, these implementations are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art. At the same time, the protection scope of the present invention includes but is not limited to the following:
[0036] In the following examples, the mass percentages of geopolymer microsphere components are as follows: powder: gangue: fly ash: slag are 25-50 parts: 25-50 parts: 25-50 parts. Water glass is a commercially available chemical agent, with a modulus of 1.2-1.8, a solid content of 34wt%, a Baume degree of 40, and a water glass addition amount of 30wt%-50wt% of solid powder. The sodium nitrite, sodium dodecyl sulfate, and ammonium chloride used are analytically pure, and the mass ratio of the foaming system addition amount to the powder is 0.5-1:150. Xanthan gum or hydroxyethyl cellulose; citric acid are commercially available chemical agents. The curing temperature of the blast drying oven is 80°C, and the curing time is 1.0h.
[0037] The water used in the following examples is tap water.
[0038] The concentration of the wastewater (hexavalent chromium) in the embodiment of the present invention is determined by the absorption peak intensity of an ultraviolet spectrophotometer at 544 nm.
[0039] Example 1
[0040] The component formula of the foaming system itself in this embodiment is: 100 parts of sodium nitrite; 10 parts of sodium dodecyl sulfate, 100 parts of ammonium chloride, 5 parts of foam stabilizer xanthan gum, and 25 parts of catalyst citric acid.
[0041] The geopolymer microspheres of this embodiment include coal gangue, fly ash, slag, an alkali activator, and a foaming system. The mass fractions of coal gangue and fly ash in the powder are 25% (25 g) and 25% (25 g) respectively, and the mass fraction of slag is 50% (50 g);
[0042] The modulus of water glass in the alkali activator is 1.4, and the addition amount is 30wt% (30g) of the powder.
[0043] The mass ratio of the added amount of the foaming system to the powder is 0.5:150, which is 0.33g.
[0044] After the coal gangue, fly ash and slag are evenly mixed in the above proportions, water glass and foaming system are added in proportion, mechanically stirred evenly, poured into a silicone mold, put into a sealed bag, and cured in a blast drying oven; then the mold is taken out of the blast drying oven and cured at room temperature; after the curing is completed, the porous adsorbent is crushed into 30-50 mesh for use.
[0045] Take 50 ml, 50 mg / L, 25°C wastewater (hexavalent chromium) solution as the target pollutant, weigh 100 mg of porous adsorbent and add it to the solution, stir for 120 minutes, and detect it using a UV spectrophotometer.
[0046] Example 2
[0047] The component formula of the foaming system itself in this embodiment is: 150 parts of sodium nitrite; 30 parts of sodium dodecyl sulfate, 120 parts of ammonium chloride, 10 parts of hydroxyethyl cellulose as a foam stabilizer, and 40 parts of citric acid as a catalyst.
[0048] The geopolymer microspheres of this embodiment include coal gangue, fly ash, slag, an alkali activator, and a foaming system. The mass fractions of coal gangue and fly ash in the powder are 30% (30 g) and 30% (30 g) respectively, and the mass fraction of slag is 40% (40 g);
[0049] The modulus of water glass in the alkali activator is 1.4, and the amount added is 40wt% (40g) of the powder.
[0050] The mass ratio of the added amount of the foaming system to the powder is 1:150, which is 0.66g.
[0051] After the coal gangue, fly ash and slag are evenly mixed in the above proportions, water glass and foaming system are added in proportion, mechanically stirred evenly, poured into a silicone mold, put into a sealed bag, and cured in a blast drying oven; then the mold is taken out of the blast drying oven and cured at room temperature; after the curing is completed, the porous adsorbent is crushed into 30-50 mesh for use.
[0052] Take 50 ml, 100 mg / L, 25°C wastewater (hexavalent chromium) solution as the target pollutant, weigh 200 mg of porous adsorbent and add it to the solution, stir for 120 minutes, and detect it using a UV spectrophotometer.
[0053] Example 3
[0054] The component formula of the foaming system itself in this embodiment is: 150 parts of sodium nitrite; 30 parts of sodium dodecyl sulfate, 120 parts of ammonium chloride, 10 parts of hydroxyethyl cellulose as a foam stabilizer, and 40 parts of citric acid as a catalyst.
[0055] The geopolymer microspheres of this embodiment include coal gangue, fly ash, slag, an alkali activator, and a foaming system. The mass fractions of coal gangue and fly ash in the powder are 30% (30 g) and 30% (30 g) respectively, and the mass fraction of slag is 40% (40 g);
[0056] The modulus of water glass in the alkali activator is 1.6, and the addition amount is 50wt% (50g) of the powder.
[0057] The mass ratio of the added amount of the foaming system to the powder is 1:150, which is 0.66g.
[0058] After the coal gangue, fly ash and slag are evenly mixed in the above proportions, water glass and foaming system are added in proportion, mechanically stirred evenly, poured into a silicone mold, put into a sealed bag, and cured in a blast drying oven; then the mold is taken out of the blast drying oven and cured at room temperature; after the curing is completed, the porous adsorbent is crushed into 30-50 mesh for use.
[0059] Take 50 ml, 200 mg / L, 25°C wastewater (hexavalent chromium) solution as the target pollutant, weigh 500 mg of porous adsorbent and add it to the solution, stir for 120 minutes, and detect it using a UV spectrophotometer.
[0060] Example 4
[0061] The component formula of the foaming system itself in this embodiment is: 100 parts of sodium nitrite; 10 parts of sodium dodecyl sulfate, 100 parts of ammonium chloride, 5 parts of foam stabilizer xanthan gum, and 25 parts of catalyst citric acid.
[0062] The geopolymer microspheres of this embodiment include coal gangue, fly ash, slag, an alkali activator, and a foaming system. The mass fractions of coal gangue and fly ash in the powder are 50% (50 g) and 25% (25 g) respectively, and the mass fraction of slag is 25% (25 g);
[0063] The modulus of water glass in the alkali activator is 1.8, and the addition amount is 40wt% (40g) of the powder.
[0064] The mass ratio of the added amount of the foaming system to the powder is 0.9:150, that is, 0.6g.
[0065] After the coal gangue, fly ash and slag are evenly mixed in the above proportions, water glass and foaming system are added in proportion, mechanically stirred evenly, poured into a silicone mold, put into a sealed bag, and cured in a blast drying oven; then the mold is taken out of the blast drying oven and cured at room temperature; after the curing is completed, the porous adsorbent is crushed into 30-50 mesh for use.
[0066] Take 50 ml, 10 mg / L, 25°C wastewater (hexavalent chromium) solution as the target pollutant, weigh 50 mg of porous adsorbent and add it to the solution, stir for 120 minutes, and detect it using a UV spectrophotometer.
[0067] The degradation effect of the wastewater (hexavalent chromium) of Examples 1-4 was tested, and the results are shown in Table 1.
[0068] Table 1 Degradation effect of wastewater (hexavalent chromium) in the embodiment
[0069]
[0070]
[0071] It can be seen from Table 1 that the porous adsorbent has a significant adsorption effect on hexavalent chromium, which is due to its excellent pore structure and rich hydroxyl structure on the surface, and the porous adsorption and electrostatic adsorption of hexavalent chromium are significant. Therefore, according to the components of the present invention, a porous adsorbent with a relatively high pore area and excellent adsorption effect of hexavalent chromium pollutants can be obtained.
[0072] In summary, the present invention discloses a method for preparing a porous adsorbent for removing hexavalent chromium from wastewater and an application method thereof. The treatment method comprises the following steps: first, preparing a porous adsorbent capable of efficiently adsorbing hexavalent chromium, then adding the porous adsorbent to wastewater containing hexavalent chromium, and stirring for a certain period of time, so as to efficiently remove pollutants such as hexavalent chromium from the wastewater. The porous adsorbent prepared by the present invention is polymerized by solid wastes such as coal gangue and fly ash, and a foaming system and a foam stabilizing system are added during the polymerization process. The obtained porous adsorbent has a rich pore structure and a high pore area. The adsorbent surface has a large number of grooves and has fine pores inside. The specific surface area is large and can provide more adsorption active sites. The present invention can simply and efficiently adsorb and remove hexavalent chromium in wastewater by preparing the porous adsorbent, has extremely low cost, is easy to operate, and has excellent application prospects.
[0073] Thus far, various embodiments of the present invention have been described, and the above description is exemplary, not exhaustive, and is not limited to the described embodiments. Without departing from the scope and spirit of the described embodiments, many modifications and variations are within the scope of the present invention for those of ordinary skill in the art.
Claims
1. A porous adsorbent for removing hexavalent chromium from wastewater, characterized in that: Including the following ingredients: Powder: coal gangue, fly ash, slag; wherein the coal gangue, fly ash and slag account for 25-50 parts, and the total of the three is 100 parts. Alkali activator: water glass, the mass ratio of water glass to powder is 3-5:10; Foaming system: sodium nitrite, sodium dodecyl sulfate, ammonium chloride, foam stabilizer, catalyst, wherein the foaming system contains 100-150 parts of sodium nitrite, 10-30 parts of sodium dodecyl sulfate, 100-120 parts of ammonium chloride, 5-10 parts of foam stabilizer, and 25-40 parts of catalyst; The foam stabilizer is xanthan gum or hydroxyethyl cellulose; The catalyst is citric acid; The mass ratio of the foaming system to the powder is 0.5-1:
150.
2. A porous adsorbent for removing hexavalent chromium from wastewater according to claim 1, characterized in that: The mass percentages of the components in the coal gangue are: SiO2: 60%-75%, Al2O3: 20%-28%, CaO: 0.1%-0.8%, K2O: 3%-3.8%, TiO2: 1%-1.5%; The mass percentages of the components in the fly ash are: SiO2: 50%-55%, Al2O3: 20%-29%, CaO: 0.01%-0.5%, K2O: 1%-1.8%, TiO2: 2%-2.5%; The mass percentage of each component in the slag is: SiO2: 30%-35%, Al2O3: 10%-16%, CaO: 30%-42%, K2O: 0.1%-0.5%, TiO2: 1%-1.7%.
3. A porous adsorbent for removing hexavalent chromium from wastewater according to claim 1, characterized in that: The particle size of the coal gangue is less than 0.075 mm and needs to be calcined at 600-800° C. for 4-6 hours before use; the particle size of the fly ash is less than 0.075 mm and the particle size of the slag is less than 0.075 mm.
4. A porous adsorbent for removing hexavalent chromium from wastewater according to claim 1, characterized in that: The water glass has a modulus of 1.2-1.8, a solid content of 34 wt %, and a Baume degree of 40.
5. The method for preparing a porous adsorbent for removing hexavalent chromium from wastewater according to claim 1, characterized in that: The steps include: Step S1: Mix coal gangue, fly ash and slag in proportion to obtain powder A; Step S2: stirring water glass and then standing to obtain an alkaline activator; Step S3: mixing sodium nitrite, sodium dodecyl sulfate, ammonium chloride, a foam stabilizer and a catalyst in proportion to obtain a foaming system; Step S4: adding the powder A obtained in step S1 to the alkali activator obtained in step S2; after mixing, mechanically stirring to obtain a mixed slurry B; Step S5: adding the foaming system obtained in step S3 to the mixed slurry B obtained in step S4, and then mechanically stirring to obtain a mixed slurry C; Step S6: then pouring the mixed slurry C into a silica gel mold, putting it into a sealed bag, and curing and solidifying it in a blast drying oven; Step S7: The mold is taken out from the blast drying oven and cured at room temperature; after the curing is completed, the porous adsorbent is crushed into 30-50 meshes for standby use.
6. The preparation method according to claim 5, characterized in that: The alkaline activator is allowed to stand for 12-24 hours, the curing temperature in the blast drying oven is 50-80° C., and the curing time is 0.5-1.0 hour.
7. A method for using the porous adsorbent prepared in claim 5 in adsorbing hexavalent chromium, characterized in that: The application method comprises: mixing and stirring the porous adsorbent and wastewater; the wastewater is wastewater containing a hexavalent chromium solution.
8. The application method according to claim 7, characterized in that: The stirring time is 100-120 min.
9. The application method according to claim 7, characterized in that: The concentration of hexavalent chromium in the wastewater is 10-200 mg / L, the pH value is 1.5-10, and the peak value of the ultraviolet spectrum is 500-700 nm.
10. The application method according to claim 7, characterized in that: The dosage of the porous adsorbent is 50-500 mg / L, and the stirring rate is 800-1000 r / min.
